Bilingualism effects in pronoun comprehension: Evidence from children with autism. Issue 2 (11th November 2021) - Skrimpa, Vasileia; Spanou, Vasilina; Bongartz, Christiane; Peristeri, Eleni; Andreou, Maria; Papadopoulou, Despina
Abstract: The prevalence of autism worldwide has risen steadily in the last two decades, while bilingualism is also becoming increasingly prevalent in today's rapidly globalizing world. The current study aimed to investigate bilingualism effects in the pronoun resolution skills of children with autism in comparison to age‐matched monolingual children with autism, as well as monolingual and bilingual children of typical development ( Ν = 20 participants per group). Results showed that autistic children had general difficulty anchoring ambiguous pronouns to entities that were linguistically expressed in discourse, yet, the bilingual children with autism were more sensitive to the topicality of the entities in syntactic subject position and more prone to identify them as suitable referents of ambiguous null pronouns as compared to their monolingual peers. The findings suggest that bilingualism is not detrimental to autistic children's pronoun resolution skills. The current study aimed at determining how bilingualism influences ambiguous pronoun comprehension in children with autism as compared to bilingual and monolingual children of typical development. The findings show that bilingualism was not detrimental to the autistic children's pronoun resolution skills, further suggesting that having acquired more than one language does not exacerbate autistic children's deficits in the comprehension of pronouns. Lay Summary: The current study aimed at determining how bilingualism influences ambiguous pronoun comprehension in children with autism as compared to bilingual and monolingual children of typical development. The findings show that bilingualism was not detrimental to the autistic children's pronoun resolution skills in, further suggesting that having acquired more than one language does not exacerbate autistic children's deficits in the comprehension of pronouns.